The Decriminalisation of Sex Work as a Human Rights Issue in South Africa - Khumalo, Thandoluhle (University of the Witwatersrand, Johannesburg, 2023)
This research report argues that sex work be decriminalised in South Africa to avoid further human rights violations against sex workers, with a particular focus on the human rights violations perpetuated against sex workers during the COVID19 pandemic. To make these arguments the report sets out the background of sex work and the origins of the various laws that have emerged over the years to regulate sex work in South Africa. Further, it investigates how sex work is governed in various countries around the world and uses New Zealand and other African countries as examples of the different approaches to legislating sex work. The report focuses on the effect of the COVID19 pandemic on female sex workers who make up the majority of sex workers. This research report grounds its assertions in the various human rights considerations found in international legal instruments as well as the Constitution of the Republic of South Africa, 1996 (Constitution) as they relate to sex work. The conclusion is that sex work should be decriminalised in South Africa as the current laws that seek to prohibit sex work in South Africa are both unconstitutional and not compliant with international human rights standards
A research report Submitted in partial fulfillment of the requirements for the degree of Master of Laws by Coursework and Research Report at the University of the Witwatersrand, Johannesburg 2023
Keywords: Decriminalisation; Sex work; Human rights; South Africa; SDG-10: Reduced inequalities